2013
DOI: 10.1053/j.gastro.2012.12.025
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Monoxide and Heme Oxygenase-1 Prevent Intestinal Inflammation in Mice by Promoting Bacterial Clearance

Abstract: BACKGROUND & AIMS Heme oxygenase-1 (HO-1) and its metabolic by-product, carbon monoxide (CO), protect against intestinal inflammation in experimental models of colitis, but little is known about their intestinal immune mechanisms. We investigated the interactions among CO, HO-1, and the enteric microbiota in mice and zebrafish. METHODS Germ-free, wild-type, and Il10−/− mice and germ free zebrafish embryos were colonized with pathogen-free (SPF). Germ-free or SPF-raised wild-type and Il10−/− mice were given i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
101
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 30 publications
1
101
0
1
Order By: Relevance
“…Additionally, we observed a significant increase in HO-1 expression in both murine macrophage RAW264.7 and hepatoma Hepa1-6 cells (unpublished data). This is consistent with previously published studies demonstrating an upregulation of HO-1 mRNA and/or protein expression in response to bacterial (29,(40)(41)(42)(43)(44)(45) or parasitic (26,27,46) infections and might be a general response of infected host cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, we observed a significant increase in HO-1 expression in both murine macrophage RAW264.7 and hepatoma Hepa1-6 cells (unpublished data). This is consistent with previously published studies demonstrating an upregulation of HO-1 mRNA and/or protein expression in response to bacterial (29,(40)(41)(42)(43)(44)(45) or parasitic (26,27,46) infections and might be a general response of infected host cells.…”
Section: Discussionsupporting
confidence: 93%
“…HO-1 is able to promote Plasmodium liver infection (26), whereas it plays a favorable role in the host during cerebral malaria (27). HO-1 also enhances bacterial clearance during CLP-mediated polymicrobial sepsis (28) and Salmonella typhimurium-induced enterocolitis (29).…”
mentioning
confidence: 99%
“…This is likely due to the increase in oxidative stress and inflammation (reviewed in Blancou et al, 2011). Onyiah et al (2013). using a colitis mouse model, showed that the enteric microbiota induces expression of HO-1 in mice and zebrafish.…”
Section: Anti-inflammatory Response To Salmonella Infectionmentioning
confidence: 99%
“…HO-1 plays a major role as a cytoprotective and antiinflammatory protein in many diseases (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Induction of HO-1 is necessary for the resolution phase of wound healing, including amelioration of inflammation, proliferation, and protection against apoptosis (35).…”
mentioning
confidence: 99%